The Cost-Effectiveness of Dolutegravir in Combination with Tenofovir and Lamivudine for HIV Therapy: A Systematic Review - Aprilianti S; Utami AM; Suwantika AA; Zakiyah N; Azis VI (Dove Medical Press, 2024)
Santi Aprilianti,1,* Auliasari M Utami,1 Auliya A Suwantika,1- 3,* Neily Zakiyah,1,2,* Vanji Ikhsan Azis4 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 2Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, Indonesia; 3Center for Health Technology Assessment, Universitas Padjadjaran, Bandung, Indonesia; 4Research and Development, PT Kimia Farma Tbk, Bandung, Indonesia*These authors contributed equally to this workCorrespondence: Auliya A Suwantika, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jalan Ir. Soekarno KM.21, Jatinangor, 45363, Indonesia, Email auliya@unpad.ac.idAbstract: The World Health Organization (WHO) recommends dolutegravir (DTG), a human immunodeficiency virus (HIV) medicine, as the first- and second-line treatment for all populations because, when compared to an efavirenz (EFV) regimen, plus two nucleoside reverse transcriptase inhibitors (NRTIs) has demonstrated significant effectiveness in HIV suppression in persons. This study aims to review evidence of the cost-effectiveness of DTG in combination with tenofovir and lamivudine compared with the standard of care for HIV therapy. The systematic review involved searching electronic databases for articles published between January 2018 and May 2022. Electronic database sources include PubMed, ScienceDirect, and EBSCO for articles on DTG in combination with tenofovir and lamivudine as subjects with cost-effectiveness outcomes. The inclusion criteria in this systematic review were studies about the cost-effectiveness analysis (CEA) of DTG in combination with tenofovir and lamivudine, written in English. A total of 145 articles were identified from three databases. After removing nine duplicates, 142 articles were screened by title and abstract, excluding 123 articles. After a full-text screening of 19 articles, five articles were selected for further analysis. Five articles reviewed in sub-Saharan Africa, India, and China implemented different modelling methods for CEA but produced similar results. The results of these studies demonstrate that it is more cost-effective than standard care for HIV treatment. The study conducted in sub-Saharan Africa from 2018 to 2020 showed a cost-effective result with disability-adjusted life years averted (DALY averted) by 83%; in India, it resulted in incremental cost-effectiveness ratio (ICER) $130 per year of live-saved (YLS); and a study in China found that dolutegravir plus tenofovir and lamivudine led to 0.006 incremental quality-adjusted life years (QALYs) with cost savings of $64. The DTG regimen is cost-effective and recommended for HIV therapy in all studies that provide results.Keywords: cost-effectiveness, antiretroviral therapy, human immunodeficiency virus, dolutegravir, efavirenz